2022
DOI: 10.1111/1468-0009.12593
|View full text |Cite
|
Sign up to set email alerts
|

Patient Identification of Diagnostic Safety Blindspots and Participation in “Good Catches” Through Shared Visit Notes

Abstract: Patients and families can identify clinically relevant errors, including “blindspots”—safety hazards that are difficult for clinicians or organizations to see. Health information transparency, including patient access to electronic visit notes, now federally mandated in the US and the subject of policy debate worldwide, creates a new opportunity to engage patients in diagnostic safety. However, not all patients access notes. Patient identification of blindspots in their notes underscores the need to systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 111 publications
(187 reference statements)
0
8
0
Order By: Relevance
“…As sarcoma patient care is shared by 2 institutions with independent EHRs, additional efforts would be needed to accurately transfer and record reports in the patient’s electronic charts. Additionally, patient engagement in their own health record keeping could further ensure the accuracy of the data within EHRs [9] . Institution specific patient portals along with independent person-centered health platforms would allow patients to partner and participate in their own EHR upkeep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As sarcoma patient care is shared by 2 institutions with independent EHRs, additional efforts would be needed to accurately transfer and record reports in the patient’s electronic charts. Additionally, patient engagement in their own health record keeping could further ensure the accuracy of the data within EHRs [9] . Institution specific patient portals along with independent person-centered health platforms would allow patients to partner and participate in their own EHR upkeep.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports on the rate of documentation errors in patient charts [8] , [9] , [10] have suggested that approximately 40 % of patient charts contained serious mistakes, of which diagnosis misalignment is the most common mistake category. Using a Natural Language Processing method, Warner et al observed 83.6 % of cancer patients had discordant cancer stages within their charts [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, in medical education, SOAP note content is an ideal means of assessing clinical reasoning 18 . Further, patient access to documentation improves diagnosis by identifying “diagnostic safety blindspots.” 19 One study found that many patients acted on the blindspots they identified by reviewing shared notes, resulting in “good catches” that may prevent potential negative consequences 19 . SOAP notes are an effective tool that aids in the complex process of clinical reasoning.…”
Section: Counterpointmentioning
confidence: 99%
“…29 Innovations to engage patients in diagnosis therefore require a focus on promoting equity and principled data collection to examine disparities in use. 16,36 To date little is known about how to engage patients and families of diverse races, ethnicities, or language preferences in the DxP.…”
Section: Background and Significancementioning
confidence: 99%